Altered gene expression by sedaxane increases PSII efficiency, photosynthesis and growth and improves tolerance to drought in wheat seedlings - Ajigboye, Olubukola O.; Lu, Chungui; Murchie, Erik H.; Schlatter, Christian; Swart, Gina; Ray, Rumiana V. (Elsevier, 2017)
Succinate dehydrogenase inhibitor (SDHI) fungicides have been shown to increase PSII efficiency and photosynthesis under drought stress in the absence of disease to enhance the biomass and yield of winter wheat. However, the molecular mechanism of improved photosynthetic efficiency observed in SDHI-treated wheat has not been previously elucidated. Here we used a combination of chlorophyll fluorescence, gas exchange and gene expression analysis, to aid our understanding of the basis of the physiological responses of wheat seedlings under drought conditions to sedaxane, a novel SDHI seed treatment. We show that sedaxane increased the efficiency of PSII photochemistry, reduced non-photochemical quenching and improved the photosynthesis and biomass in wheat correlating with systemic changes in the expression of genes involved in defense, chlorophyll synthesis and cell wall modification. We applied a coexpression network-based approach using differentially expressed genes of leaves, roots and pregerminated seeds from our wheat array datasets to identify the most important hub genes, with top ranked correlation (higher gene association value and z-score) involved in cell wall expansion and strengthening, wax and pigment biosynthesis and defense. The results indicate that sedaxane confers tolerant responses of wheat plants grown under drought conditions by redirecting metabolites from defense/stress responses towards growth and adaptive development.